2016
DOI: 10.12788/emed.2016.0046
|View full text |Cite
|
Sign up to set email alerts
|

The Orlando Nightclub Shooting: Firsthand Accounts and Lessons Learned

Abstract: These emergency physicians describe what it was like in the ED on the night of the Orlando mass-casualty incident, and what they learned from the experience that can help other EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[1][2][3][4] Recent MCIs have shown that limited lifesaving interventions, primarily hemorrhage control, swift extrication, and immediate transport, should be priorities for care. [5][6][7][8] Training first responders to integrate response skills into a dynamic, unstable, and active disaster is challenging and difficult to simulate. Further complicating first responder training is the lack of a standard triage protocol or use of protocols that are outdated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Recent MCIs have shown that limited lifesaving interventions, primarily hemorrhage control, swift extrication, and immediate transport, should be priorities for care. [5][6][7][8] Training first responders to integrate response skills into a dynamic, unstable, and active disaster is challenging and difficult to simulate. Further complicating first responder training is the lack of a standard triage protocol or use of protocols that are outdated.…”
Section: Introductionmentioning
confidence: 99%
“…As mass casualty incidents (MCIs) proliferate in the United States, we increasingly rely on skilled first responders, who deliver accurate and timely triage and to reduce overall morbidity and mortality of victims 1–4 . Recent MCIs have shown that limited lifesaving interventions, primarily hemorrhage control, swift extrication, and immediate transport, should be priorities for care 5–8 . Training first responders to integrate response skills into a dynamic, unstable, and active disaster is challenging and difficult to simulate.…”
Section: Introductionmentioning
confidence: 99%
“…These mass casualty events create surges of victims that overwhelm healthcare systems, leading to the preventable loss of human lives. Averting surges that jeopardize the emergent care of victims requires a workforce of emergency personnel who are well trained in the fundamentals of disaster response, 3 including targeted hemorrhage control, swift extrication, minimal interventions, and immediate transport to the appropriate receiving centers 4–8 …”
Section: Introductionmentioning
confidence: 99%
“…Averting surges that jeopardize the emergent care of victims requires a workforce of emergency personnel who are well trained in the fundamentals of disaster response, 3 including targeted hemorrhage control, swift extrication, minimal interventions, and immediate transport to the appropriate receiving centers. [4][5][6][7][8] Conventional training of first responders for mass casualty events involves 1 of 3 methods: (1) live, large-scale simulations of mass casualty incidents (MCIs) that use manikins and actors cast in a temporary setting 9,10 ; (2) table-top drills that resemble board games 11 ; and (3) lectures or presentations on mass casualty response, sometimes followed by facilitated discussions about treating specific patient victims. 12 The large-scale simulations are the most realistic and effective but are resource heavy, expensive to construct, available for a limited time (usually 1 day), and are overly reliant on human evaluators to assess participants.…”
Section: Introductionmentioning
confidence: 99%